Evolution of tax revenue in the years 2008 to 2013 result of reform in the regulatory framework for income tax in Colombia (2014)
The paper analyzes relevant aspects of the Colombian regulatory framework of income tax, ranging from 2008 to 2013.Se shows the income and complementary tax at the national level; presenting a synthesized analysis related to the changes that have been generated with tax reforms in Colombia in the mentioned period. The paper shows the development of evasion, avoidance and tax planning as shocking elements to raise income tax. The national tax collection under study yields a greater focus on large taxpayers. Finally, suggestions are proposed for tax collection management DIAN (National Tax and Customs), mainly with complaints citizen participation and encouragement of a culture of taxation; training of public servants in tax legislation, the importance of accountability as a tool for monitoring by the supervisory bodies and the community.